Empirical Exchange Rate Models of the Nineties Are Any Fit to Survive? - Cheung, Yin-Wong (International Monetary Fund, 2004)
We reassess exchange rate prediction using a wider set of models that have been proposed in the last decade. The performance of these models is compared against two reference specifications-purchasing power parity and the sticky-price monetary model. The models are estimated in first-difference and error-correction specifications, and model performance is evaluated at forecast horizons of 1, 4, and 20 quarters, using the mean squared error, direction of change metrics, and the ""consistency"" test of Cheung and Chinn (1998). Overall, model/specification/currency combinations that work well in one period do not necessarily work well in another period